Հայատառ թուրքերեն տպագիր բառարանները - Ստեփանյան, Հասմիկ («Զանգակ - 97»)
There are about 25 two-language, 30 three-language, 12 four-language, 10 multilanguage Arm-lettered dictionaries published also 15 two-language and multilanguage phrase-books and 10 other dictionaries, which were a part of Arm-lettered Turkish literature. Though Arm-lettered literature lived a fall in the middle of 20 ' th century but most o f these dictionaries were in USE and kept their cintetic value.
Keywords: Լեզվաբանություն; Բառարանագիտություն